Asuhan Kebidanan Komprehensif pada Ny. U di RSUD Kota Makassar - Rabiatuladawiyah; Husnah, Nurul; Sharief, Suchi Avnalurini (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Health problems in Indonesia are mainly caused by maternal and infant mortality. Pregnancy, childbirth, newborn, and postpartum are physiological conditions that may threaten the life of the mother and baby and can even cause death. One effort that can be made is to implement a comprehensive midwifery care model. Comprehensive obstetric care is a holistic approach to obstetric services that covers all aspects of women's reproductive health. To improve the quality of health, the author contributes by providing comprehensive obstetric care ranging from pregnancy, childbirth, newborn, postpartum, and family planning. The author employs the 7-step Varney management method and documentation, utilizing SOAP format, of the provision of midwifery care. Data collection is carried out through interviews, observations, physical examinations, supporting examinations, and documentation. Comprehensive obstetric care for Mrs. U G1P0A0, gestational age 36 weeks 5 days, as well as pregnancy visits carried out 6 times, and no signs of danger symptoms were found in pregnancy. During childbirth, oxytocin induction is given. Newborn babies do not cry immediately, muscle tone is weak, have bluish skin color, are female gender, have a body length of 42 cm, a weight of 3600 grams, a head circumference of 32.5 cm, a chest circumference of 32 cm, and during postpartum visits are made 3 times, with the postpartum period taking place normally. Then, the method of contraception chosen is the contraceptive device in the womb. The author hopes that patients can increase their insight to detect possible complications and that the author maximizes skills in providing comprehensive care.